Implementation of Moringa Leaf Pudding Processing Strategy to Increase the Added Value of MSME Products in Ketapang II Village - Nico Sebayang; Rahmad Dhavin Prasetya; Riski Rachmad Romadhan; Rina Ambarwati; Dian Mutia; Sela Marselina; Kristian Anggara; Revi Marizka; Reza Alfarezi Prayoga; Ismi Nur Hayati; Hendry Endrasyah (Altifani Journal: International Journal of Community Engagement, 2025)
Micro, Small and Medium Enterprises (MSMEs) are one of the main pillars of the Indonesian economy, capable of absorbing labor and improving community welfare. Moringa leaves (Moringa oleifera) are highly nutritious plants with potential to be developed as raw materials for processed food. Ketapang II Village has natural resources in the form of moringa leaves that have not been optimally utilized, as most residents only use them as vegetables for daily consumption. This study aims to develop a strategy for processing moringa leaves into pudding products with high selling value for local MSME actors. The method used is a qualitative approach through direct observation and interviews, covering the stages of production, packaging, and product marketing. Moringa leaf pudding is marketed in the village environment at a price of IDR 5,000.00/pcs and generates an added value of around 60% from production capital. The results show that this innovation can increase consumer interest in processed products made from moringa leaves and create new business opportunities for the community of Ketapang II Village.